A quasi-experimental evaluation of advance care planning improves consistency between elderly individuals and their surrogates regarding end-of-life care preferences: Development and application of a decision aid with cartoon pictures. Issue 4 (April 2021) - Ke, Li-Shan; Hu, Wen-Yu; Chen, Ching-Yu; Liu, Chieh-Yu; Chiu, Tai-Yuan
Highlights: The intervention improved the consistency in EOL care. A decision aid with cartoon pictures may support the discussion of EOL care. College-educated elderly individuals were more likely to be mastered themselves. Large family affect the consistency in EOL care. Surrogates' predictions were worse when they did not consider ACP. Abstract: Objective: This study sought to develop a decision aid with cartoon pictures and evaluate its effectiveness in increasing consistency between elderly individuals and their surrogates regarding end-of-life care. Methods: A pre-post quasi-experimental design was adopted using the Life Support Preferences Questionnaire. The intervention had two components: (1) increasing participants' knowledge of medical treatments related to end-of-life care, and (2) sharing their end-of-life wishes. The experimental group received an intervention, whereas the control group received usual care. Results: A total of 110 participants in 55 pairs of elderly individuals with average aged 86.4 and their surrogates (27 in the experimental group, 28 in the control group) were recruited from a veterans hospital in northern Taiwan. Nearly 90 % of elderly individuals were male. The multiple linear regression showed that the inconsistent gap between elderly individuals and their surrogates in the experimental group decreased 12 points than the control group after controlling the covariances (B = −12.116, p = 0.032). Conclusion: The intervention improved the consistency between elderly individuals and their surrogates regarding end-of-life care. Practice implications: A decision aid with cartoon pictures may support the discussion of end-of-life care in older Asian populations.